Breeding Latin American Tigers : Operational Principles for Rehabilitating Industrial Policies - Devlin, Robert; Moguillansky, Graciela (Santiago, Chile: United Nations Economic Commission for Latin America and the Caribbean and Washington, DC: World Bank, 2012)
The specific structure of the book is as follows: chapter one reviews the current situation of Latin America, which historically has been a laggard in economic performance. Chapter two introduces the first principle: the urgency of developing a medium- to long-term strategy for productive transformation based on industrial policies. Chapter three focuses on the principle that strategies for productive transformation with modern industrial policies should rest on effective, locally grown public-private alliances. Chapter four introduces and illustrates principles 3-6, which focus on the 'how' of public sector leadership in the public-private alliance and the formulation and execution of strategies. Chapter five presents and illustrates principles 7-11, which are concerned with the public sector management of support programs and incentives. Chapter six shifts the focus to Latin America. It reviews the past and current nature of development strategies in the region, pointing to their strengths and weaknesses as tools for guiding productive transformation. In chapter seven, the author follow the path of principles 3-11 to critically evaluate the nature of public sector leadership in strategy execution and the modes for managing programs and incentives. Finally, chapter eight presents our central conclusions, which suggest that while some countries in Latin America have been planting the seeds of these 11 principles gleaned from our extra-regional success cases, they still have considerable work to do.